Catalytic Kinetics of the Schiff Base Metal Complexes Bearing Side Chain of Cyclic morpholine in Carboxylic Ester Hydrolysis - 张述林 李敏娇 欧忠文 陈国需 刘富安 谢家庆 (Chinese journal of chemistry, 2007)
It has been reported that two Schiff base transition metal complexes bearing the side chain of the morpholine ring were synthesized and characterized, and two complexes with the same base agent but different metal ions were used as a simulant hydrolase in the catalytic hydrolysis of p-nitrophenyl picolinate in this paper. The mechanism of PNPP catalytic hydrolysis is proposed and supported by the results of the spectral analysis and the kinetic calculation. A kinetic mathematical model, applied to the calculation of the kinetic and thermodynamics parameters of PNPP catalytic hydrolysis, has been established on the foundation of the mechanism proposed. The result of the study shows that the two complexes have a good catalytic activity in PNPP catalytic hydrolysis, and the rate of the PNPP catalytic hydrolysis was increased with the increase of the pH values in the buffer solution and affected by the polarization effect of metal ion of the complexes.